2010
DOI: 10.1590/s0102-311x2010000300004
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização de demandas judiciais de fornecimento de medicamentos "essenciais" no Estado do Rio de Janeiro, Brasil

Abstract: Recognition of the right to health raises two practical issues IntroduçãoAs leis e recomendações internacionais reconhecem o direito à saúde como um direito humano, estando ele incluso nas leis constitucionais de alguns países. O acesso aos medicamentos essenciais é considerado por alguns autores como integrante deste direito 1,2,3 .No Brasil, o direito à saúde está disposto nos artigos 6 o , 196 o a 200 o da Constituição Federal brasileira, como um direito social, a ser garantido por meio de políticas, que, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
84

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(134 citation statements)
references
References 9 publications
1
49
0
84
Order By: Relevance
“…The first year of the publications included in the review was 2005, and there was a peak in the years 2010 and 2011. The data refer to studies done in the states of Pernambuco 5 , Rio Grande do Sul 2,6 , Minas Gerais 7,8 , Rio de Janeiro 9,10,11,12 , and São Paulo 13,14,15,16,17 , besides one article that collected data directly from the Ministry of Health in Brasilia 18 . The studies that examined the most lawsuits (between 2,000 and 2,927 cases) were done in the states of São Paulo, Rio de Janeiro, and Santa Catarina 7,12,14,16,19 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The first year of the publications included in the review was 2005, and there was a peak in the years 2010 and 2011. The data refer to studies done in the states of Pernambuco 5 , Rio Grande do Sul 2,6 , Minas Gerais 7,8 , Rio de Janeiro 9,10,11,12 , and São Paulo 13,14,15,16,17 , besides one article that collected data directly from the Ministry of Health in Brasilia 18 . The studies that examined the most lawsuits (between 2,000 and 2,927 cases) were done in the states of São Paulo, Rio de Janeiro, and Santa Catarina 7,12,14,16,19 .…”
Section: Resultsmentioning
confidence: 99%
“…Three articles 2,6,10 (17.6%) examined petitions for advance relief or other types of court injunctions, and the results were the following: two studies showed 100% of such petitions 6,10 and one 98% 2 . The majority of the studies (76.5%; n = 13) collected specific data to determine whether there was more than one defendant in the suits, four conducted this analysis 2,6,9,10 , in two of them the defendants were states and municipalities 9,13 and in the others the defendants were states, municipalities, and the Federal Government 2,6 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations